PENGARUH PENERAPAN METODE SURVEY, QUESTION, READ, RECITE AND REVIEW (SQ3R) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN DURIAN TARUNG PADANG TAHUN PELAJARAN 2012/2013 - Delvita, Devi Netria; Rismen, Sefna; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
The research is in background by low students understanding of mathematical concept. This research aimed to determine whether students understanding of mathematical concepts using Survey, Question, Read, Recite And Review (SQ3R) method better than using the conventional learning in grade VIIIÂ MTsN Durian Tarung Padang.This type of research is experiment research with a random design on the subject. The population in this research were all students grade VIII MTsN Durian Tarung Padang. The sampling technique is random sampling. Technique analysis date used is test-t one side. The data analisys which tvalue= 2.52 is greather than ttable = 1.65. It can be concluded that students understanding of mathematical concepts using Survey, Question, Read, Recite And Review (SQ3R) method better than using the conventional learning in grade VIIIÂ MTsN Durian Tarung Padang with the level of confidenceÂ 95%.